Regulatory framework in 3D printing. Issue 4 (October 2017) - Bhargav, Aishwarya
3D printing or additive manufacturing has induced a paradigm change in the healthcare space. Medical devices, drugs and even cells may be processed using 3D printing. Despite the patient-specific advantages that 3D printing offers, several companies hesitate to incorporate it into the manufacturing process owing to the ambiguity in the regulatory framework. There exists confusion on whether the printer itself needs to be treated as a medical device and regulated or whether it is the end product that needs to be regulated. This article aims to elaborate the regulatory pathways that may be considered for 3D printed devices.